(untitled) (Journal of International Studies, 2025)
Pan-Malaysian Islamic Party (PAS) is a prominent political party in Malaysia that has long championed Malay nationalism. This study examines PAS’s political connections and approach in addressing Muslim issues on a global scale, mainly through the lens of Malay nationalism. A qualitative methodology was employed to analyse key documents, speeches, and policies of PAS leaders over the years. The findings revealed that PAS has actively sought to align its nationalist agenda with broader Islamic causes, forging connections with like-minded organisations and movements internationally. PAS has positioned itself as a defender of Malay rights and interests while advocating for implementing Islamic principles in governance and society. The party’s interpretation of Malay nationalism is deeply rooted in its Islamic ideology, seeking to reconcile ethnic and religious identities. This study contributes to the understanding of how a regional political party, such as PAS navigates the complex interplay between nationalism, religion, and global affairs. It highlights PAS’s efforts to project its influence beyond the Malaysian context and situate the Malay nationalist struggle within the broader framework of the Muslim ummah. The implications of such an approach for national unity, regional dynamics, and the party’s long-term political trajectory are also discussed.